2010
DOI: 10.1111/j.1442-9071.2010.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors among schoolchildren in Shiraz, Iran

Abstract: Compared with other reported rates, the prevalence of myopia in the schoolchildren of Shiraz is similar to that in most places excluding East Asian countries, and that of hyperopia is in the mid range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
7
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 25 publications
9
82
7
3
Order By: Relevance
“…The prevalence of astigmatism, myopia, and hyperopia, has been reported in numerous studies worldwide 12345. Similar to myopia, astigmatism is influenced by genetic and ethnic actors and its prevalence has been reported from 30% among old people in Myanmar to 77% in Indonesia 6789.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of astigmatism, myopia, and hyperopia, has been reported in numerous studies worldwide 12345. Similar to myopia, astigmatism is influenced by genetic and ethnic actors and its prevalence has been reported from 30% among old people in Myanmar to 77% in Indonesia 6789.…”
Section: Introductionmentioning
confidence: 97%
“…Astigmatism is the most common refractive error in certain countries such as Indonesia,6 Taiwan,8 and Japan,9 and approximately half of the people in these areas suffer from astigmatism. Age, gender, genetics, and even environmental factors have been shown to affect astigmatism in different studies 1579101112131415161718. Astigmatism has some major differences compared to myopia and hyperopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As refractive errors are the major causes of mild to moderate visual impairment in patients, knowledge about the prevalence of refractive error would be of great help in planning public health strategies (4). Some studies indicated that in children the prevalence of hyperopia decreased and that of myopia significantly increased (P < 0.001) by getting older (5)(6)(7)(8)(9)(10). In contrast with the increment of myopia with age, some studies reported that the reduction of myopia and increment of hyperopia with aging (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, hyperopia is more common than myopia among Iranians. [10][11][12][13] Current study showed that only 42.3% out of all error of refraction cases are wearing correctable glasses which is much higher than another study [14] which stated that there was no awareness among the students and parents regarding the consequences of uncorrected vision problems. This statement has been proved, when we observe the number of students wore glasses.…”
Section: Discussionmentioning
confidence: 80%